PENGARUH BEBAN PAJAK TANGGUHAN, PERENCANAAN PAJAK DAN AKTIVA PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Lutfi M. Baraja; Yuswar Zainul Basri; Vertari Sasmi (Jurnal Akuntansi Trisakti, 2017)
This study aimed to examine the effect of deferred tax expense, tax planning, and the deferred tax assets to earnings management. The independent variable of this research is deferred tax expense, tax planning and deferred tax assets, the dependent variable of this study is the disclosure of Earnings Management. The sample used in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2013-2015 as many as 46 companies by using purposive sampling method. This study uses multiple methods of analysis using SPSS 23. These results indicate that in partial deferred tax expense, tax planning and deferred tax assets has positive influence on the disclosure of earnings management.